Preparation of Alkali Activated Cementitious Material by Upgraded Fly Ash from MSW Incineration - Chen, Hongwei; Zhao, Runbo; Zuo, Wu; Dong, Guanghui; He, Dongyang; Zheng, Tengfei; Liu, Changqi; Xie, Hao; Wang, Xinye (International journal of environmental research and public health, 2022)
Utilization of municipal solid waste incineration fly ash (MSWI-FA) can avoid land occupation and environmental risks of landfill. In this paper, MSWI-FA was used to prepare alkali activated cementitious materials (AACMs) after two-step pretreatment. The ash calcination at 450 °C removed 93% of dioxins. The alkali washing with 0.2 g NaOH/g ash removed 89% of chlorine and retained almost 100% of calcium. The initial setting time of AACMs was too short to detect for 20% of MSWI-FA addition, and the prepared block had extensive cracks and expansion for CaClOH and CaSO4 inside. Alkaline washing pretreatment increased the initial setting time by longer than 3 min with 30% ash addition and eliminated the cracks and expansion. The significance of the factors for compressive strength followed the modulus of alkali activator > silica fume amount > alkaline washing MSWI fly ash (AW-MSWI-FA) amount. When the activator modulus was 1.2, 1.4 and 1.6, the blocks with 30% of AW-MSWI-FA had a compressive strength of up to 36.73, 32.61 and 16.06 MPa, meeting MU15 grade. The leaching test shows that these AACM blocks were not hazardous waste and almost no Zn, Cu, Cd, Pb, Ba, Ni, Be and Ag were released in the leaching solution.